?BIOMETRICAL ANALYSIS OF SOME METRICAL TRAITS OF GOSSYPIUM HIRSUTUM L. COMBINING ABILITY (Biological Sciences - PJSIR, 1995)
An experiment was conducted to estimate the combining ability in 8 cultivars of G. hirsutum L. General combiningability (GCA) mean squares for testers were significant for boll number only, whereas GCA for lines and SCAfor hybrids were highly significant for boll number and seedcotton yield. The larger proportion of variance for GCArevealed that the nature of gene action was predominantly additive for these traits. S-12 for boll number and seedcottonyield. CRIS-7 A for sympodia, boll number and seed cotton yield, and CYTO-127 and CYTO- I30 for seed cottonyield proved to be the best general combiners. The crosses S-12 x CYTO-127 and BH-36 x CRIS-54 manifestedhighly significant SCA effects for boll number and seed cotton yield per plant.